Product Characteristic Uncertainty in Supply Chains : Cases from the Food Industry - Eliot Simangungsong (ITB, 2012)
The food industry is a complex supply chain, where the path of a specific food product may vary and the supply chains within the food industry may have different structures from each other. Anatother important characteristic of the food industry is the high frequency of new product Introductions; this increases choice for consumers and initiates uncertainty related to product issues such as high product failure rates, short product life cycles and high inventory holding costs. Consequently, it is important to understand product characteristic as a source of supply chain uncertainty, how they can be managed and the resulting impact on performance. This research present a review of the available literature on supply chain uncertainty and related fields ,hghlights that although product characteristic has been identified as a source of uncertainty, insufficient empirical evidence has been presented. Multi-case study reseach, using semi structured interviews, has been conducted across a group of inter-related companies in the food industry in Indonesia tto investigate the role of product characteristic in creating uncertainty. THe result of analysis helps to refine the concept and provides a basis for detecting and managing product characteristic uncertainty, critical in the current competitive context.